Adherence to insulin treatment in insulin-naive type 2 diabetic patients initiated on different insulin regimens - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2015)
Objective: We aimed to evaluate adherence to insulin treatment in terms of treatment persistence and daily adherence to insulin injections among insulin-naive type 2 diabetic patients initiating insulin therapy with basal (long acting), basal-bolus, and premixed insulin regimens in a tertiary endocrinology outpatient clinic. Methods: A total of 433 (mean age of 55.5 +/- 13.0 years; 52.4% females) insulin-naive type 2 diabetic patients initiated on insulin therapy were included in this questionnaire-based phone interview survey at the sixth month of therapy. Via the telephone interview questions, patients were required to provide information about persistence to insulin treatment, self-reported blood glucose values, and side effects; data on demographics and diabetes characteristics were obtained from medical records. Results: Self-reported treatment withdrawal occurred in 20.1% patients, while 20.3% patients were nonadherent to daily insulin. Negative beliefs about insulin therapy (24.1%) and forgetting injections (40.9%) were the most common reasons for treatment withdrawal and dose skipping, respectively. Younger age (49.5 +/- 15.0 vs 56.4 +/- 12.0 years) (P=0.001) and shorter duration of diabetes (4.8 +/- 4.3 vs 8.8 +/- 6.3 years) (P=0.0008) and treatment duration (5.2 +/- 2.4 vs 10.7 +/- 2.4 months) (P=0.0001) were noted, respectively, in discontinuers vs continuers. Basal bolus was the most commonly prescribed insulin regimen (51.0%), while associated with higher likelihood of skipping a dose than regular use (61.3% vs. 46.0%, P=0.04). Conclusions: Persistence to insulin therapy was poorer than anticipated but appeared to be higher in patients with the basal bolus regimen. Negative perceptions about insulin therapy seemed to be the main cause for poor adherence in our cohort.
Keywords: type 2 diabetes; insulin treatment adherence; basal-bolus insulin regimen; premixed insulin regimen; PREMIXED INSULIN; GLYCEMIC CONTROL; BASAL-BOLUS; GLOBAL ATTITUDES; OPEN-LABEL; BARRIERS; PERSISTENCE; THERAPY; VIAL/SYRINGE; MEDICATION